Putting Muhammad’s (2019) framework of historically responsive literacy to work in Middle Grades Language Arts - Kelsey L Benson; Matt Brown (Middle Grades Review, 2022)
Now more than ever, it is imperative that middle grades literacy curriculum invites “students to learn about matters of personal, social, moral, and ethical significance” (Bishop & Harrison, 2021, p. 27). Using a framework for culturally and historically responsive literacy, Muhammad advocates in her groundbreaking text, Cultivating Genius (2019), for curriculum that provides middle grades students space to learn about matters of significance, to name and critique injustice and oppressive structures, and to develop their agency to cultivate a better world. In this essay, the authors discuss the possibilities and challenges that we – one a former interrelated resource teacher currently enrolled in a PhD program, the other a current 8th grade Language Arts teacher – experienced while collaborating to design an 8th grade literacy unit using Muhammad’s equity framework for culturally and historically responsive literacy. This article will begin with an overview of Muhammad’s four-pronged framework—identity, skills, intellect, and criticality—followed by a discussion of how this informed our curricular decision-making, particularly around the inclusion of fiction texts that center the voices and perspectives of queer, trans, and Black and Brown folx. Though readers of this story will be disappointed to find no happy ending to our earnest endeavors, we aim to provide a case study in what Freire (1970) called “problem-posing” education, wherein students are empowered to critically analyze the world around them in ways that challenge the hegemony of a dominator culture that aims at every turn to silence their voices.
Keywords: historically responsive literacy; Middle Grades ELA; critical perspectives; middle school